Editorial Foreword IJSLS Volume 4 Number 1 - Irianto, Sulistyowati (The Indonesian Journal of Socio-Legal Studies, 2025)
The late “Ibu” Keebet von Benda-Beckmann made a significant contribution to the development of legal anthropology, particularly in Indonesia, where she is regarded as a pioneer of the field. Together with her husband, Franz von Benda-Beckmann, she conducted research in Indonesia for more than 40 years, inspiring and laying the foundation for many Indonesian legal scholars to conduct research in legal anthropology and socio-legal studies. The Benda-Beckmann's works have become key references for legal anthropologists, proponents of legal pluralism, and socio-legal scholar around the world, to the extent that their theories and methodologies—particularly those related to the concept of legal pluralism—have become part of the universal canon of legal anthropology.